PERAN ORGANISASI PIMPINAN ANAK CABANG IKATAN PELAJAR NAHDLATUL ULAMA IKATAN PELAJAR PUTERI NAHDLATUL ULAMA (IPNU IPPNU) DALAM MEMBENTUK KARAKTER NASIONALISME PADA REMAJA DI KECAMATAN TAMAN KABUPATEN SIDOARJO - Farid Anwar; Muhammad Turhan Yani (Universitas Negeri Surabaya (Unesa), 2023)
The problem of teenagers today is not something that can be underestimated because teenagers are an asset to the nation because they are the next generation who will continue leadership in the country of Indonesia, but teenagers are currently experiencing a problem, namely the decline in the character of nationalism, namely 1. Decreased socialization 2. Activeness in the success of the event statehood 3. And the willingness to spread national insights from themselves they prefer to be silent and play cellphones even more interested in foreign culture than their own nation. The purpose of this research is to find out the role of the Branch Leaders of the Nahdlatul Ulama Student Association and the Nahdlatul Ulama Girls Student Association, Taman District Sidoarjo Regency in forming the character of nationalism in adolescents in Taman Subdistrict, Sidoarjo Regency and knowing what are the obstacles experienced by this study using descriptive qualitative methods with data sources from interviews with informants, the results of the study show that the Lead The leadership of the Nahdlatul Ulama Student Association Branch and the Nahdlatul Ulama Female Student Association, Taman Subdistrict, Sidoarjo Regency has a role in establishing the character of nationalism in Taman Subdistrict, which is carried out through various work programs, some of which are internal and external, including the loyalty period of members, training of young cadres and future members. Introduction to the school environment. Internal activities are more specific to members while external activities are for youth outside the members of the IPNU IPPNU management, Taman District